1972
DOI: 10.1159/000259789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Bicarbonate-Phosphate Combination, without and with Fluoride, on the Growth and Dental Caries in the Rat

Abstract: A total of 49 rats was littermate-distributed into three dietary groups when 21 days old. The control group (C) was fed a cariogenic nutritionally adequate high- sucrose diet for 40 days. The second group (BP) received the same diet as group C except that 4% of the sucrose component of the diet was replaced by a combination Phosphate, dietary NaHCO3 + KH2PO4 (mole ratio 9.82/1). The third group (BPF) was fed the same diet as group BP except that NaF was also added to the sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…This resulted in greater body weights of the fluoridated diet groups. These findings are in agreement with those of Luoma et al [1972b] who added 10 ppm fluoride to a cariogenic rat diet and also noted a significant weight gain when com pared to control animals fed a nonfluoridated diet. Fluoride is not only deposited in developing teeth, but is also deposited in the bones of growing ani mals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This resulted in greater body weights of the fluoridated diet groups. These findings are in agreement with those of Luoma et al [1972b] who added 10 ppm fluoride to a cariogenic rat diet and also noted a significant weight gain when com pared to control animals fed a nonfluoridated diet. Fluoride is not only deposited in developing teeth, but is also deposited in the bones of growing ani mals.…”
Section: Discussionsupporting
confidence: 91%
“…Fluoride is not only deposited in developing teeth, but is also deposited in the bones of growing ani mals. Luoma et al [1972b] demonstrated that the femurs of rats fed a diet with 10 ppm fluoride con tained ten times the amount of fluoride when com pared to the control group. The femurs were also longer in the animals with fluoride in the diet.…”
Section: Discussionmentioning
confidence: 97%
“…LUOMA, HURSKAINEN Sc ISOKANGAS (24), LuO'MA & LUO'M.^ (23) and TuRTOLA & LuOMA (43) found that inclusion of NajCOj or NaHCO, with alkali orthophosphate into sugar could more or less correct the drop of plaque pH and the inorganic phosphate which tend to decrease during or after carbohydrate (6,11,16,25,30,35,36). Similar findings on elevation of plaque phosphate have also been Rat experiments (26, 27,29) showed that marked caries reductions were obtained by bicarbonate-phosphate or bicarbonate-phosphate-fluoride combinations mixed into the dietary sugar without causing calcifications of the kidneys (22).…”
mentioning
confidence: 55%
“…1 btit it must be low, as tlie amount of vehicle ingested was small. The trend of enhanced dental calculus formation in the test grotip may be pardy attributable to the bicarbonatephosphate, as this combination tended slightly to increase the calculus formation in rats (29). However, the amount of calculus was rather low in the test group and it may not as such introduce any contraindication for use of the bicarbonate-phosphate additions.…”
Section: Bicarbonate-phosphatementioning
confidence: 88%
See 1 more Smart Citation